2013
DOI: 10.1111/ijtd.12004
|View full text |Cite
|
Sign up to set email alerts
|

Wages and skills utilization: effect of broad skills and generic skills on wages in Singapore

Abstract: Many people go for training to upgrade their skills which is hoped to pave the way for better pay. But what are the kinds of skills that really affect wages? Employers have emphasized the value of generic skills such as interpersonal and communication skills, teamwork and problem solving. Does possession of these skills translate to at least the same or better wages as compared with having broad skills represented by educational qualifications and job-related training? This paper, arising from the research pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Green also found no numerical skills link with pay; Ramos et al . () also confirm a similar result with the Singaporean Skills Utilisation study: communication and problem‐solving skills remain valued primarily in professional jobs.…”
Section: The Nature Of Employability Skillssupporting
confidence: 81%
See 1 more Smart Citation
“…Green also found no numerical skills link with pay; Ramos et al . () also confirm a similar result with the Singaporean Skills Utilisation study: communication and problem‐solving skills remain valued primarily in professional jobs.…”
Section: The Nature Of Employability Skillssupporting
confidence: 81%
“…Green (1999) examined the links between pay and employability skills utilization and found that IT skills are highly valued, compared with other employability skills. Green also found no numerical skills link with pay; Ramos et al (2013) also confirm a similar result with the Singaporean Skills Utilisation study: communication and problem-solving skills remain valued primarily in professional jobs.…”
Section: The Skills Surveys Approachsupporting
confidence: 70%
“…Finally the survey included 15 skills. It consists of 10 most significant skills which were supplemented by 5 chosen on the basis of the research author's subjective decision (they were chosen from the list of 16 additional skills provided by The University of Kent (Ramos et al, 2013) The second stage was choosing the kind of industry which would be covered by the research and the chosen one was the pulp and paper industry (PPI) -which produces pulp, paper, board and other cellulose-based products. The main steps of the process are pulping, papermaking and paper finishing.…”
Section: Methodsmentioning
confidence: 99%
“…As a result the literature provides examples of sets including e.g. 42 (Ramos et al, 2013), 36 (Chan et al, 2017), 26 (Top 10 skills..., 2018) and 10 (Griffin, & Annulis) generic skills. When the skill rankings are developed they may be influenced by the chosen procedure of gathering opinions or the choice of the respondents (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Requirements for selecting an appropriate sustainability index lie in the following points (Böhringer & Jochem, ): The extensive connection to the definition of sustainability of the certain aspect, that is, through relevant literature review (Pezzey, ). Selection of indicators that will result in a holistic result for the aspect, that is, through relevant literature review and advice from experts (Custance & Hillier, ). Availability and reliability of data that can be quantified over a period of time, that is, through the practicality through field surveys (Stehling, ). Thus, the indicators were developed based on a review of the literature (Ramos, Ng, Sung, & Loke, ; Bangladesh Labour Rules, ) on each major component, through FGD, and they were assessed on the basis of the practicality of collecting the needed data through field surveys. Table includes an explanation of how each subcomponent was quantified, the survey question used to collect the data, the original source of the survey question.…”
Section: Measuring Sustainability Vulnerability Indexmentioning
confidence: 99%